DENSITY MANAGEMENT DIAGRAMS FOR STANDS OF Eucalyptus grandis W. Hill RS, BRAZIL - Marangon,Gabriel Paes (2017)
ABSTRACT Density Management Diagrams (DMD) contribute to the forester, as they allow the understanding of the current situation of the stand, in addition to helping predict its future conditions. The aim of this study is to develop Density Management Diagrams for Eucalyptus grandis Hill ex Maiden, which will serve as auxiliary models for this species, and to establish appropriate density variation, or management zone, for managing stands to be demarcated on the diagram. Full density stands will be used for the study area. The construction of the diagram will be based on the maximum density line (A-line) obtained from fully stocked stands. From this line, stand density indices (B-line and C-line) will be generated in a gradual and proportional manner. The management zone will be made according to the required thinning weight, and afterwards it will generate Density Management Diagram (DMD). This study allowed us to find a possible adjustment of stand density of Eucalyptus grandis Hill, which is fundamental for management of the stand.